6ER-026 Spectrum of heart failure in 16 sub-Saharan African countries: treatments and in-hospital outcome. Issue 1 (23rd March 2023) - Cavagna, P; Kouam Kouam, C; Diop, IB; Limbole, E; Allawaye, L; Takombe, JL; Traore, AK; N'Guetta, R; Ikama, MS; Jouven, X; Antignac, M
Abstract : Background and Importance: Heart failure (HF) is the most common primary diagnosis for patients admitted to hospital with heart disease in sub-Saharan Africa (SSA). However, little is known about the management of HF in hospitalisation in SSA. Aim and Objectives: To describe in hospital drugs strategies to manage HF in 36 cardiovascular (CV) departments. Material and Methods: We conducted a transversal and longitudinal study in CV departments of 36 hospital (public and private) in 16 SSA countries. The February study is an ongoing observatory included all inpatients in February from each year since 2016. Data including socio-demographic and clinical characteristics, CV risk factors, causes of admission, medication and length of stay were collected during hospitalisation by physicians. Patient wealth index was assessed by physicians as low, middle and high according to patient capacity to afford hospitalisation. All analyses were performed with random effect on countries and through scripts developed in the R software 4.0.3. Results: Overall, 2084 patients were admitted for HF in the February study. HF representing 47.9% of all patients included. The mean age was 57 ± 17.4 years and 53.8% were men. Proportions of patients admitted for HF varied across countries from 21.4% in Burundi to 66% in Congo (p<0.01). Average length of stay in hospitals was 11 days and mortality rate was 13%. Among HF patients, 74% of patients had CV risk factors and hypertension was reported in 55.8% of patients. During hospitalisation, 88.8% of patients were treated with diuretics followed by angiotensin-converting enzyme inhibitors (ACEI) (61.8%), anticoagulant (47.8%) and beta blockers (BB) (34.6%) ( figure ). Monotherapy were used in 14%, combination of two drugs, three drugs and four drugs strategies were used in 35%, 33% 12% respectively. Diuretics were mostly prescribed in patient with low wealth index whereas ACEI, BB and anticoagulant in high wealth index (p<0.05). Conclusion and Relevance: HF treatment access varied significantly across countries and according to patient wealth index. References and/or Acknowledgements: Conflict of Interest: No conflict of interest.